Ro Helps a Small Utility Improve Water Supply. Issue 7 (1st July 2015) - Briley, David S.; Pierce, Maggie H.; Irwin, Patrick
Abstract : North Carolina's northeastern Currituck County implemented reverse osmosis at its water treatment plants to provide a reliable barrier against contaminants and maintain a sustainable potable water supply for its community.